Rational Asymmetric Development, Piketty and Poverty in Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
An April 2015 World Bank report on the Millennium Development Goal poverty target has revealed that extreme poverty has been decreasing in all regions of the world with the exception of Africa. This study extends the implications of Thomas Piketty's celebrated literature from developed countries to the nexus between developed nations and African countries by building on responses from Rogoff (2014) and Stiglitz (2014), post Washington Consensus paradigms and underpinnings from Solow-Swan and Boyce-Fofack-Ndikumana. The central argument presented is that the inequality problem is at the heart of rational asymmetric development between rich and poor countries. Piketty has shown that inequality increases when the return on capital is higher than the growth rate, because the poor cannot catch-up with the rich. We argue that when the return on political economy (or capitalism-fuelled illicit capital flight) is higher than the growth rate in African countries, inequality in development increases and Africa may not catch-up with the developed world. As an ideal solution, Piketty has proposed progressive income taxation based on automatic exchange of bank information. The ideal analogy proposed in tackling the spirit of African poverty is a comprehensive commitment to fighting illicit capital flight based on this. Hence, contrary to theoretical underpinnings of exogenous growth models, catch-up may not be so apparent. Implications for the corresponding upward bias in endogenous development and catch-up literature are discussed.
Keywords: B20; F35; F50; O19; O55; 330; Piketty; Inequality; Foreign aid; Capital flight; Development